Longitudinal Vibration and Stability Analysis of Conveying Belt of Belt Conveyor - Man Zhang; Haoxuan Jin; Yongqiang Yang; Yuanhu Cheng; Taisong Guo (Jixie chuandong)
The differential equation of longitudinal vibration of the belt conveyor with stable conveying speed is established based on Kelvin-Voigt viscoelastic theory. The differential quadrature method is used to discrete the vibration equation and boundary conditions. The eigenvalue equation containing the conveying speed and quality variation function of the longitudinal vibration of the belt conveyor is obtained. The relationship between dimensionless complex frequency of longitudinal vibration and dimensionless conveying speed is analyzed. The results show that the second-third order flutter instability occurs in the case of uniform quality， but the first-second， third-fourth order flutter instability occur in the case of non-uniform quality. This conclusion provides a theoretical basis for the stable operation of belt conveyor.